Tradition meets modernity: learning traditional building using artificial intelligence / Sri Winiarti ... [et al.] - Winiarti, Sri; ., Sunardi; Ahdiani, Ulaya; Pranolo, Andri (Universiti Teknologi MARA, 2022)
Indonesia is a country that is famous for its culture, arts, traditional crafts, and even traditional houses. This diversity is reflected in each region by having a unique culture as an icon of the area. Therefore, the diversity of arts and culture needs to be preserved, so that it can be used as education and study material for scientific development. This study aims to create a model of cultural preservation through an application to identify the types of traditional buildings in Indonesia. This research focuses on the preservation of traditional Javanese houses because they have many types with uniqueness in terms of topology and also ornaments. Each building model looks similar visually, but actually different because each ornament and topological form has special characteristics. This is an education for students and the general public to know the history of the building. The concept applied in identifying the type of building uses the concept of Deep Learning as one of the fields of Artificial Intelligence (AI). The research begins with the acquisition of building object data, image analysis, development of application as an educational tool for students or the community, and the last is evaluation. The data was taken by taking pictures directly of traditional Javanese buildings in Indonesia using cameras, smartphones, and drones. The total of 1330 images were captured consisting of traditional Javanese house ornaments which are Joglo and Kalang. Based on the tests carried out to recognize building objects, the system successfully able to recognize building objects with an accuracy of 99.5%. In terms of education in recognizing building design and culture, this application was tested on students, it can increase students' knowledge on building history by 97%.